Virulence Factors of the Periodontal Pathogens: Tools to Evade the Host Immune Response and Promote Carcinogenesis - Linah A. Shahoumi; Muhammad H. A. Saleh; Mohamed M. Meghil (Microorganisms, 2023)
Periodontitis is the most common chronic, inflammatory oral disease that affects more than half of the population in the United States. The disease leads to destruction of the tooth-supporting tissue called periodontium, which ultimately results in tooth loss if uncured. The interaction between the periodontal microbiota and the host immune cells result in the induction of a non-protective host immune response that triggers host tissue destruction. Certain pathogens have been implicated periodontal disease formation that is triggered by a plethora of virulence factors. There is a collective evidence on the impact of periodontal disease progression on systemic health. Of particular interest, the role of the virulence factors of the periodontal pathogens in facilitating the evasion of the host immune cells and promotion of carcinogenesis has been the focus of many researchers. The aim of this review is to examine the influence of the periodontal pathogens Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), Porphyromonas gingivalis (P. gingivalis), and Fusobacterium nucleatum (F. nucleatum) in the modulation of the intracellular signaling pathways of the host cells in order to evade the host immune response and interfere with normal host cell death and the role of their virulence factors in this regard.